DEPICTING PRAGMATIC PRESUPPOSITIONS IN YOUTUBE ADVERTISEMENTS - Anit Pranita Devi (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2020)
Presupposition is one of influential elements of advertising language due to its persuasive function to grab viewers’ attentions to buy a product. This study investigated the types of presupposition triggers in ten Indonesian skippable Youtube advertisements. The data from the advertisements particularly were analyzed in terms of presupposition triggers employed and mapped in percentage. Qualitative and descriptive quantitative approaches were employed in analyzing the data. The result showed that existential presupposition was the most frequent presupposition appeared in the Youtube advertisements analyzed in this study. The logical reason underlying the frequent use of existential presupposition is to inform the viewers about the existence of the product and attract the viewers in a simple way.  It can be concluded that advertisers can utilize presuppositions to create a more attractive advertisements to gain the viewers’ interests and accordingly purchase the advertised product. Keywords: Presupposition, Presupposition triggers, Youtube advertisements